Distilling agency in BIM-induced change in work practices. Issue 3 (24th March 2021) - Akintola, Adeyemi Ayodele; Venkatachalam, Senthilkumar; Root, David; Oti, Akponanabofa Henry
Abstract : Purpose: Critics of claims about building information modeling's (BIM's) capability to revolutionize construction industry practices describe it as overhyped, fallacious and therefore suggest that there is need for a more critical examination of its change impacts. Others have posited that the changes BIM induces are evolutionary rather than revolutionary. In this vein, the purpose of this paper was to undertake a careful analysis of the nature of such changes to distil actual changes that happened, and the type of agency that brings such changes about. Design/methodology/approach: Drawing from appropriate qualitative research strategies, data was collected through key informant interviews from consulting organizations in South Africa that have implemented BIM within their organizations and on projects. Findings: Changes in organizations' work practices were evident in their workflows, formal/informal methods of interaction, norms, leadership and authority structures, remuneration and the way work was conceived or conceptualized. Furthermore, changes in organizational work practices do not solely occur through the direct agency of the BIM tool's implementation. Instead, BIM-induced change occurs by delegated, conditional and needs-based agency – which are not mutually exclusive. Originality/value: The nature of changes in professional work practices could be misconstrued as being solely because of the actions of agents who actively participate in implementing BIM. The discussion in the literature has, therefore, been advanced from general to specific theoretical understandings of BIM-induced change, which emphasize the need for construction stakeholders to actively participate in developing the innovations that drive change in the industry rather than hand the power to drive change to BIM authoring and management application developers who have less stake in the industry.